An Exercise in the Theory of Heterogeneous Capital Accumulation - Caton, C.; Shell, K. (Review of Economic Studies, 1971)
C. Caton, K. Shell; An Exercise in the Theory of Heterogeneous Capital Accumulation12, The Review of Economic Studies, Volume 38, Issue 1, 1 January 1971,